Organizational Justice Model across Seven Countries - Cozma, Irina (Psihologia Resurselor Umane, 2020)
In general research that has examined organizational justice (OJ) across countries has failed to prove first the measurement equivalence of their measures, thus making their results questionable. The present study focuses on the measurement equivalence of the three factor OJ model in seven countries (four languages) with the aim of seeing if the three factor model of OJ holds across these countries. The basic question that we want to answer is „Do respondents from different countries interpret the OJ measure in a conceptually similar manner?”. In subsidiary we looked at the effect of language and geographical location. Our findings indicate that OJ is equivalent across all seven countries (configural, metric, scalar and uniqueness equivalence). Different sub-models are discussed (grouped by language and geographical location). Results indicated that neighbor countries that share the same language have a better fit of the three factors OJ model. Key words: measurement equivalence, organizational justice, countries, CFA.